Effect of Fungi Bioaugmentation on Solidification and Stabilization (S/S) Method of Industrial Wastewater Sludge-Removal of Heavy Metal - Mahmud Fuzi, Adhhiyyah; Mohd Kamil, Nor Amani Filzah (Recent Trends in Civil Engineering and Built Environment, 2021)
The rapid growth industrial development and urbanization increases the production of industrial wastewater sludge that contains heavy metals, pathogens and organic compounds can impact on human health and the environment. This study aims to treat the industrial wastewater sludge by using the combination of solidification and stabilization (S/S) method and fungi bioaugmentation method, which specifies in measuring the effect of fungi bioaugmentation on S/S method based on the compressive strength of the S/S matrices and leaching behaviour of heavy metals concentrations. The materials used in sludge remediation were Portland cement to act as a binder and Aspergillus brasiliensis ATCC 16404 as the degrading agent. The experimental work involved in this study includes compressive strength test, leaching test (TCLP) and measure the concentration of heavy metals by using ICP-MS equipment followed British standards (BS) and United States Environmental Protection Agency (US EPA). After 7 days, the effect of fungi bioaugmentation and S/S method on Sample D recorded the lowest compression strength and only Arsenic samples passed the leaching test. Thus, increase the curing period up to 72 or 90 days can be implemented to improve the results.